2011
DOI: 10.1371/journal.pone.0015862
|View full text |Cite
|
Sign up to set email alerts
|

Pathology of Camel Tuberculosis and Molecular Characterization of Its Causative Agents in Pastoral Regions of Ethiopia

Abstract: A cross sectional study was conducted on 906 apparently healthy camels slaughtered at Akaki and Metehara abattoirs to investigate the pathology of camel tuberculosis (TB) and characterize its causative agents using postmortem examination, mycobacteriological culturing, and multiplex polymerase chain reaction (PCR), region of difference-4 (RD4)-based PCR and spoligotyping. The prevalence of camel TB was 10.04% (91/906) on the basis of pathology and it was significantly higher in females (χ2 = 4.789; P = 0.029).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
65
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(85 citation statements)
references
References 27 publications
15
65
5
Order By: Relevance
“…The Ethiopian Somalia camel rearing community in Shinile such as Issa is almost pure camel herders and keep their camels in open land just making a fence with thorny plants around it during night time, but in case of Oromia camel rearing areas where most of the camels are kept in close confinement with cattle, especially during night camels and cattle are kept together. Close confinement of camels and cattle together might be the source of cross infection (Mamo et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Ethiopian Somalia camel rearing community in Shinile such as Issa is almost pure camel herders and keep their camels in open land just making a fence with thorny plants around it during night time, but in case of Oromia camel rearing areas where most of the camels are kept in close confinement with cattle, especially during night camels and cattle are kept together. Close confinement of camels and cattle together might be the source of cross infection (Mamo et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…M. bovis strains were also isolated by Donchenko et al (1975) in Russia from bulked samples of raw dromedary milk. Recent studies in Ethiopian abattoirs also reported isolation of M. bovis (Mamo et al, 2011) and M. tuberculosis from tissue lesions (Gumi et al, 2012;Zerom et al, 2012). Five to twelve percent abattoir-based prevalence of tuberculosis compatible lesions (TCL) in dromedary camels slaughtered at Dire Dawa abattoir in Eastern Ethiopia and in Addis Ababa abattoir were recorded (Mamo et al, 2009;Mamoet al, 2011;Zerom et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted in Egypt, Sudan, India, Somalia, Kazakhstan and Ethiopia has shown that tuberculosis is occurring in camels (Fassi Fehri, 1987). Camel TB has been described in Egypt (Mustafa, 2013), the United Arab Emirates (Kinne et al, 2006;Wernery et al, 2007;, Pakistan, Kazakhstan (Elmossalami et al, 1971), Somalia, Nigeria (Abubaker et al, 2014, and Ethiopia (Mamo et al, 2009;Zerom et al, 2013 (Kinne et al, 2006;Elmossalami et al, 1971;Mamo et al, 2011;Zerom et al, 2013, Rhodes et al, 2015.…”
Section: Introductionmentioning
confidence: 99%
“…The same study by Berg et al [7,[67][68][69] identified a clonal complex of Mycobacterium bovis isolated at high frequency from cattle in Uganda, Burundi, Tanzania, and Ethiopia. Other studies showed M. bovis isolates in Ethiopia were also reported [70][71][72][73][74]. M. bovis and M. tuberculosis molecularly characterized and summarized by Brudey et al [74,75].…”
Section: Indicate Epidemiological Status Of a Strainmentioning
confidence: 99%